Strategi Pengembangan Kompetensi Sumber Daya Manusia Angkutan Multimoda di PT. Masaji Kargosentra Tama - Tampubolon, Antoni; Indrawan, Rully; Maimunah, Siti (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the current state of HR competencies in the multimodal transport sector at PT. Masaji Kargosentra Tama (PT. MKT ) and to formulate relevant and applicable HR development strategies. Additionally, it examines the implementation of multimodal HR competency development in Indonesia. This research employs a descriptive qualitative approach with data collected through in-depth interviews with key informants from managerial and operational levels. The analysis uses the SWOT approach to formulate strategies based on the company’s strengths, weaknesses, opportunities, and threats. The findings reveal that although PT. MKT has a complete multimodal organizational structure and holds legal status as a Multimodal Transport Business Entity (BUAM), its HR competencies are not yet fully aligned with the Indonesian National Work Competency Standards (SKKNI). HR training and development have remained general and are not specifically targeted toward multimodal transport competencies, including those available through internal platforms such as SICU and Udemy. The resulting strategy from the SWOT analysis prioritizes the Strengths–Opportunities (SO) strategy, focusing on organizational structure optimization, internal training enhancement, and HR development based on legal compliance and professional certification systems. The implementation of HR competency development in multimodal transport across Indonesia remains suboptimal due to the limited scope of SKKNI, the absence of certification schemes and standardized training programs, and the lack of specialized Professional Certification Institutions (LSPs), resulting in a significant gap between industry needs and HR readiness in Multimodal Transport Development, SWOT Analysis.